Difference in Perfusion Parameters Between Gastric Cancer and Gastric Stromal Tumors: Evaluation With Oral Contrast Plus Contrast-Enhanced Ultrasonography - Wang, Xiaohua; Kou, Hongju; He, Huiliao; Lu, Mingdong; Zhou, Lingling; Wang, Liang (Frontiers in Oncology, 2020)
Objective: To explore the difference of perfusion parameters between gastric cancer (GC) and gastric stromal tumors (GST) by using double contrast-enhanced ultrasonography (DCEUS). Methods: We retrospectively reviewed 149 patients with histologically confirmed gastric lesions (80 patients with GC and 69 patients with GST). DCEUS were performed in all patients in GC group and GST group before surgery. The cine loops of DCEUS of all cases were analyzed. The perfusion parameters including arrival time (AT), time to peak (TTP), basal intensity (BI) and peak intensity (PI) were obtainedvia a program designed for auto-tracking contrast quantification (ACQ). The between-group differences in these parameters were compared. Results: According to time-intensity curve (TIC) analysis, GC group had faster arrival time (AT), higher peak intensity (PI) than GST group(P<0.05). In contrast, thedifference in basal intensity (BI) and peak time (TTP) between the groups was not significant (P> 0.05) Conclusion: AT and PI differ significantly between GC group and GST group. As a new method, DCEUS has value for the differential diagnosis of GC and GST.